Septoplasty techniques- conventional versus endoscopic: our experience - Rajguru, Renu; Singh, Inderdeep; Galagali, J. R.; Singh, Anubhav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Deviated nasal septum is one of the most common disorders in human beings, which may lead to symptoms of nasal obstruction, headache, epistaxis, hyposmia, and post nasal drip. DNS correction may also be required to gain access during intranasal procedures like endoscopic sinus surgery, endoscopic dacryocystor-hinostomy and skull base surgery. The technique of septoplasty has evolved over the decades with a tendency towards more conservative and precise surgery. Over the last few decades endoscopic septoplasty has become increasingly popular. Methods: It was a cross-sectional comparative study done to compare the efficacy of endoscopic septoplasty with conventional septoplasty, conducted at a tertiary care centre over a period of 3 years. Records of 100 patients of nose and PNS disorders with DNS who were operated either by conventional or by endoscopic technique were studied. The patients were studied for the improvement in their symptoms, anatomical correction and intra-operative/post-operative complications. Results: Endoscopic septoplasty group patients showed better symptomatic relief, lesser incidence of residual anterior /posterior deviation and persistent spur and less complications as compared to the conventional septoplasty group. Conclusions: In our study we found more clientele satisfaction and lesser rate of complications in endoscopic septoplasty group. We recommend all ENT specialists to be trained in nasal endoscopic septoplasty technique as it offers many advantages such as more precision in post nasal spurs with less flap tears, it can be tailor made according to the disease and can be combined with various endoscopic surgeries.